2020
DOI: 10.1038/s41598-020-74614-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci associated with canopy temperature in soybean

Abstract: A consistent risk for soybean (Glycine max L.) production is the impact of drought on growth and yield. Canopy temperature (CT) is an indirect measure of transpiration rate and stomatal conductance and may be valuable in distinguishing differences among genotypes in response to drought. The objective of this study was to map quantitative trait loci (QTLs) associated with CT using thermal infrared imaging in a population of recombinant inbred lines developed from a cross between KS4895 and Jackson. Heritability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 86 publications
(103 reference statements)
1
21
0
Order By: Relevance
“…Research studies over the past 12 years have identified numerous QTLs from the association and linkage mapping studies that were associated with CW (Charlson et al, 2009;Abdel Haleem et al, 2012;Hwang et al, 2015Hwang et al, , 2016Kaler et al, 2017a;Steketee et al, 2020), canopy temperature (Kaler et al, 2018;Bazzer and Purcell, 2020), and C13 and O18 isotope ratios (Kaler et al, 2017b;Bazzer et al, 2020a,b). This study confirmed 87 SNPs that likely tagged 68 loci as coincident genomic regions from previous studies on CW (Charlson et al, 2009;Abdel Haleem et al, 2012;Hwang et al, 2015Hwang et al, , 2016Kaler et al, 2017a;Steketee et al, 2020), canopy temperature (Kaler et al, 2018;Bazzer and Purcell, 2020), and C13 and O18 isotope ratios (Kaler et al, 2017b;Bazzer et al, 2020a,b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research studies over the past 12 years have identified numerous QTLs from the association and linkage mapping studies that were associated with CW (Charlson et al, 2009;Abdel Haleem et al, 2012;Hwang et al, 2015Hwang et al, , 2016Kaler et al, 2017a;Steketee et al, 2020), canopy temperature (Kaler et al, 2018;Bazzer and Purcell, 2020), and C13 and O18 isotope ratios (Kaler et al, 2017b;Bazzer et al, 2020a,b). This study confirmed 87 SNPs that likely tagged 68 loci as coincident genomic regions from previous studies on CW (Charlson et al, 2009;Abdel Haleem et al, 2012;Hwang et al, 2015Hwang et al, , 2016Kaler et al, 2017a;Steketee et al, 2020), canopy temperature (Kaler et al, 2018;Bazzer and Purcell, 2020), and C13 and O18 isotope ratios (Kaler et al, 2017b;Bazzer et al, 2020a,b).…”
Section: Discussionmentioning
confidence: 99%
“…To find coincident SNPs or overlap of loci identified in this research study with those loci reported in previous studies (Charlson et al, 2009;Abdel Haleem et al, 2012;Hwang et al, 2016;Kaler et al, 2017aKaler et al, ,b, 2018Bazzer and Purcell, 2020;Bazzer et al, 2020a,b;Steketee et al, 2020), we used Bedtools Intersect Intervals Tool (Quinlan and Hall, 2010) in Galaxy with an overlapping window of ± 175 kb. This window size was chosen because the average LD across all chromosomes decayed at an average of 175 kb in the euchromatic region.…”
Section: Genome-wide Association Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative trait loci metanalysis or comparative analysis with reported QTL is normally used to confirm QTL utility for breeding or candidate gene mining (Bazzer & Purcell, 2020 ; Gong et al., 2018; Kaler et al., 2017 ; Qi et al., 2011; Van & McHale, 2017). To identify the QTL region and the linkage with known QTL, it was necessary to develop a new method of LD interval determination, based on probability of molecular markers of belonging to four predefined categories.…”
Section: Discussionmentioning
confidence: 99%